2010
DOI: 10.1007/s11224-010-9661-3
|View full text |Cite
|
Sign up to set email alerts
|

NMR elucidation of novel SQ109 derivatives

Abstract: The NMR elucidation of five novel SQ109 analogues including SQ109 is reported herein. These derivatives were synthesized as potential anti-tuberculosis candidates. One-dimensional NMR ( 1 H and 13 C) techniques show a series of overlapping signals from the methine and methylene groups of these compounds, thereby making it extremely difficult to assign all NMR signals. Twodimensional (2D) NMR techniques were instrumental in overcoming these challenges. This paper appears to be a rare report on the complete stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Compounds 1-4,reported by Onajole et al 35 , have the most de-shielded proton assigned to H-2, followed by H-4b/9b, H-1/3, Makatini et al, 36 reported di-substituents of compound 7 on C-2 with peptide linkages de-shielding the resonances of the neighbouring protons (Table 2), e.g. H-1/3 have chemical shifts around 2.66-2.74 ppm as compared to 1-6.…”
Section: Adamantanementioning
confidence: 93%
“…Compounds 1-4,reported by Onajole et al 35 , have the most de-shielded proton assigned to H-2, followed by H-4b/9b, H-1/3, Makatini et al, 36 reported di-substituents of compound 7 on C-2 with peptide linkages de-shielding the resonances of the neighbouring protons (Table 2), e.g. H-1/3 have chemical shifts around 2.66-2.74 ppm as compared to 1-6.…”
Section: Adamantanementioning
confidence: 93%
“…SQ109 (N-geranyl-N 0 -(2-adamantyl)ethane-1,2-diamine) is an ethambutol cage diamine derivative and possesses excellent activity against multi-drug-resistant (MDR) strains of tuberculosis. Onajole et al [291] report in their paper NMR elucidation of SQ109 and five new analogues, which have a potential activity against tuberculosis. Twodimensional NMR techniques assisted in resolving a series of overlapping signals from the methine and methylene groups.…”
Section: Issuementioning
confidence: 99%